Prevalence Study of Simkania Negevensis in Cooling Towers in Spain (2011)
Simkania negevensis is an obligate intracellular bacterium grouped into the order Chlamydiales. This new amoeba-resistant intracellular bacterium might represent a novel etiologic agent of bronchiolitis and community-acquired pneumonia and occurs in aquatic habitats such as drinking water and reclaimed wastewater. Another amoeba-related bacterium, Legionella pneumophila, is an etiologic agent of pneumonia transmitted by environmental aerosols or contaminated water/air cooling systems. These transmission pathways are important in the natural history of Legionellae infections and possibly other intracellular microorganisms such as Parachlamydiaceae; thus, understanding the feasibility of Simkania infection by these routes is relevant. In the present work, we investigated the prevalence of this newly identified pathogenic bacterium in cooling towers by quantitative PCR (qPCR) and its possible relationship with Legionella pneumophila co-infection. Our results show Simkania detection in 2 of 70 cooling towers analyzed. To our knowledge, this report is the first describing Simkania negevensis detection in this category of environmental water samples.